Kritikalitas Integrasi Data Kependudukan Dan Pemetaan Administrasi Dalam Meningkatkan Akurasi Perencanaan Pembangunan Nagari - Irsyad Zulfiqri; Intan Dwi Cahyani; Nina Noviana; Isnaini .; Fitria Anggraini; Indah Muliati (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
Development planning at the village level requires accurate, up-to-date, and integrated data to ensure targeted policies meet community needs. Population data based on the Family Card (Kartu Keluarga) provides important population information, but is incomplete if not linked to spatial conditions. Therefore, combining population data with administrative maps through a Geographic Information System (GIS) is a strategic step to improve the accuracy of village development planning. This study aims to analyze the importance of integrating population data and administrative mapping in supporting development planning in Kampung Batu Dalam Village. The method used is a descriptive quantitative approach with GIS-based spatial analysis, combining population data from the Family Card data collection with spatial data from the village administrative map. The results show that the integration of demographic and spatial data provides a more comprehensive picture of population distribution, inequality in access to public facilities, and areas requiring development focus. Therefore, combining population data and administrative mapping through GIS can improve the accuracy of village development planning, support data-driven decision-making, and encourage more effective, equitable, and sustainable development.